PERAN ORANG TUA, GURU, DAN MASYARAKAT DALAM MENGATASI KRISIS MORAL ANAK MADRASAH IBTIDAIYAH - Jauhari, Angelita Mustika; Devi, Alvina Fitriasari (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The moral crisis among Madrasah Ibtidaiyah students is an issue that requires serious attention. This study aims to examine the roles of parents, teachers, and the community in addressing this crisis. Using a qualitative approach, data were literatur. The findings reveal that parents play a key role in instilling moral values through home routines and exemplary behavior. Teachers contribute by integrating character education into the curriculum and creating a supportive learning environment for students’ moral development. Meanwhile, the community contributes by fostering a conducive social environment and organizing community activities that uphold moral values. The study concludes that synergy among parents, teachers, and the community is essential to cultivate a morally sound and virtuous generation. This research recommends strengthening collaboration among these three parties to effectively address the moral crisis challenges.